2018
DOI: 10.35188/unu-wider/2018/448-3
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal multipliers in South Africa: The importance of financial sector dynamics

Abstract: This study has been prepared within the UNU-WIDER project 'Southern Africa-Towards inclusive economic development (SA-TIED)'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
3
5
0
Order By: Relevance
“…These findings are broadly consistent with several studies on the impact of fiscal policy on economic activity in South Africa (e.g. Jooste et.al (2013) and those surveyed in Makrelov et. al.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…These findings are broadly consistent with several studies on the impact of fiscal policy on economic activity in South Africa (e.g. Jooste et.al (2013) and those surveyed in Makrelov et. al.…”
supporting
confidence: 93%
“…The increase in the interest bill 12 Multiplier estimates tend to be below one in the short term and negligible in the longer term in most studies. However, Makrelov et. al.…”
mentioning
confidence: 99%
“…In contrast, Fatás (2019) points to procyclical euro-area fiscal policies linked to underestimated fiscal multipliers, procyclical potential GDP estimates, and fiscal targets reliant on these estimates as the key driver of the euro-area 'fiscal policy doom loop'. Indeed, the South African evidence suggests that fiscal multipliers are underestimated in recessionary periods (e.g., Kemp 2020a; Makrelov et al 2018;Merrino 2021), but potential output (and projected tax revenue) has typically been overestimated (e.g. Hollander 2021: and citations therein), and our stylized facts presented here suggest that it is highly unlikely that fiscal policy alone can raise the potential output of the South African economy.…”
Section: Five Stylized Facts #1 Growth Is Structurally Lowmentioning
confidence: 77%
“…Second, robust estimates of tax revenue multipliers on historical data remain elusive. On one hand, Makrelov et al (2018) and Kemp (2020a) find that tax revenue increases produce negative fiscal multipliers and are thus largely counterproductive for a consolidation strategy amid weak economic growth. Indeed, relative to spending multipliers, tax multipliers are more distortionary, are subject to greater model uncertainty, and are smaller in weak economic environments.…”
Section: A4mentioning
confidence: 99%
“…Finally, a relatively new strand of the literature investigates the possibility of state-dependent multipliers. Using a stock-and-flow-consistent CGE model with a detailed financial sector for South Africa, Makrelov et al (2018) find peak spending multipliers of between 2 and 3.5 under conditions of a large negative output gap. Further empirical evidence for state-dependent multipliers can be found in, among others, Auerbach and Gorodnichenko (2012, 2013a,b, 2017 Most of these studies into state-dependent multipliers found that spending multipliers are higher during times of slack and/or constrained monetary policy.…”
Section: Government Spending Shocksmentioning
confidence: 99%